2018
DOI: 10.1021/acs.molpharmaceut.8b00340
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Transitioning Cocrystals from Bench to Bedside: Dissociation in Prototype Drug Product Environment

Abstract: Tablets containing a theophylline-glutaric acid (TG) cocrystal dissociated rapidly forming crystalline theophylline (20-30%), following storage at 40 °C/75% RH for 2 weeks. Control tablets of TG cocrystal containing no excipients were stable under the same conditions. The dissociation reaction was water-mediated, and the theophylline concentration (the dissociation product), monitored by synchrotron X-ray diffractometry, was strongly influenced by the formulation composition. Investigation of the binary compac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…PVP is highly hygroscopic 43 and the sticky and rubber-like nature of the ctz-aca/PVP sample suggests significant water uptake which may promote the decomposition of the cocrystal as reported in the literature for theophylline-glutaric acid, theophylline-isonicotinamide and caffeine-urea. [21][22][23][24] In the IR spectrum of milled nia/PVP strong shifts of the (N-H) bands are observed compared to crystalline nia which may explain why the ctz-nia cocrystal does not form in the presence of PVP. However,  for the C=O stretching vibration of nia in the IR spectrum of the free coformer and ctz-nia is 21 cm -1 suggesting also strong interactions in the cocrystal and once formed, the ctz-nia cocrystal is stable towards grinding with PVP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVP is highly hygroscopic 43 and the sticky and rubber-like nature of the ctz-aca/PVP sample suggests significant water uptake which may promote the decomposition of the cocrystal as reported in the literature for theophylline-glutaric acid, theophylline-isonicotinamide and caffeine-urea. [21][22][23][24] In the IR spectrum of milled nia/PVP strong shifts of the (N-H) bands are observed compared to crystalline nia which may explain why the ctz-nia cocrystal does not form in the presence of PVP. However,  for the C=O stretching vibration of nia in the IR spectrum of the free coformer and ctz-nia is 21 cm -1 suggesting also strong interactions in the cocrystal and once formed, the ctz-nia cocrystal is stable towards grinding with PVP.…”
Section: Discussionmentioning
confidence: 99%
“…Koranne et al investigated the effect of a range of excipients in tablets containing the theophylline-glutaric acid or theophylline-isonicotinamide cocrystals. 22,24 The cocrystal stability during storage of the tablets at 40 C and 75 % relative humidity was found to depend on the hygroscopicity and ionizability of the excipient, the solubility of the coformer and the ability of the coformer to ionize in the pH microenvironment generated by the excipient.…”
Section: Introductionmentioning
confidence: 99%
“…Although the parent cocrystal is robust when stored under identical conditions, the prototype tablet formulation dissociates into anhydrous theophylline along with the glutaric-Mg complex and stearic acid in the presence of ionizable hydrophobic excipient. 9 Kaur et al discussed the role of lattice disorder in watermediated dissociation of a caffeine−oxalic acid cocrystal. They found that disorder, induced by milling for even a short time (≤2 min), was more than sufficient to impact the physical stability of the cocrystal.…”
Section: Cocrystals Of Itraconazolementioning
confidence: 99%
“…This measure is even more relevant in the case of co-crystals since their dissociation has been reported to be influenced by the product environment, i.e., storage at high RH and temperature. 18 In particular, it has been shown that co-crystals have a higher tendency to dissociate when the solubility of the components is very different, as is the case in CTC. 19 Overall, the results reported herein helped to establish the boundaries of the physical stability of CTC, showing that its co-crystal structure confers a substantially distinctive profile versus the free combination and constituent APIs alone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Adsorption/desorption profiles, aimed at measuring the tendency for a solid to take up water vapor at constant temperature with changes in relative humidity (RH), are now determined as routine preformulation activity intended to provide an early assessment of the potential effects of moisture on the physical and chemical properties of drug candidates. This measure is even more relevant in the case of co-crystals since their dissociation has been reported to be influenced by the product environment, i.e., storage at high RH and temperature . In particular, it has been shown that co-crystals have a higher tendency to dissociate when the solubility of the components is very different, as is the case in CTC …”
Section: Introductionmentioning
confidence: 99%